The promise - Buck, Pearl S. (Pearl Sydenstricker), 1892-1973 (Moyer Bell ; Distributed in North America by Publishers Group West, 1997)
Told during the tumultuous era of the Burma campaign, this sequel to "Dragon Seed" relates how a Chinese family is divided over "the promise" that the white man will be their people's salvation.